Rastne značilnosti velikega jesena (Fraxinus excelsior L.) v Sloveniji - Kadunc, Aleš (Zbornik gozdarstva in lesarstva, 2004)
This contribution analyses the growth characteristics of common ash on four groups of sites in Slovenia. The analyses of height and diameter growth on thebasis of 162 ash trees from 20 different locations have been carried out. The results show that the fastest height growth was found in ash growing on hornbeam sites, but in the age class of over 70 growth was fastest in ash trees growing on ash sites. Ash trees on mountainous limy beech sites recordedthe slowest height growth. On the same sites, however, the diameter growth of ash is moderate, but very persistent and does not decline with age. At the age of 80-90 years the diameter growth of ash on limy beech sites exceeds the growth curves of ash from the other site groups. In fact, the diameter growth of ash on ash sites, hornbeam sites and beech sites of mixed or silicated bedrock continues to rise until the age of 50, and after that it starts decreasing, the decrease being slowest on ash sites. The current annualheight increment most often culminates before the tree is 10 years old but the mean annual height increment reaches the peak before the age of 20 years. The current annual diameter increment culminates between the age of 6 and 67 years, mostly between the age of 11 and 30 years. The mean annual diameter growth increment (MAI) culminates over a wider period than the CAI. It reaches the peak between the age of 12 and 99 years, but very rarely beforethe tree is 30 years old. The differences in height and diameter growth could be significant even within the same site units.
Keywords: Fraxinus excelsior; rast; rastišče; Slovenia; Slovenija; veliki jesen